2015
DOI: 10.2109/jcersj2.123.595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiO<sub>2</sub> addition on the synthesis of hercynite with high purity

Abstract: Hercynite as a kind of chrome-free and environmental friendly material is widely investigated. In this work, hercynite with high purity was synthesized using Fe 2 O 3 and Al 2 O 3 as raw material with SiO 2 addition under controlled temperature and atmosphere system. The phase and microstructure of the obtained product were investigated using XRD, SEM and TEM techniques. The effect of SiO 2 on the synthesis of hercynite with high purity was discussed from both theoretical and experimental aspects. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Majzlan et al suggested that, although all optimized FeAlO3 structures are higher in energy than a mechanical mixture of hematite and corundum, but the slow diffusion of ions through the structure prohibits the structure to achieve any lower-energy, ordered state, even at 1500 °K and at low temperatures, when the driving force for ordering might increase [17]. Meanwhile, MgAl2O4 can be formed from aluminum and magnesium oxides as shown in the following reaction [21]:…”
Section: Resultsmentioning
confidence: 99%
“…Majzlan et al suggested that, although all optimized FeAlO3 structures are higher in energy than a mechanical mixture of hematite and corundum, but the slow diffusion of ions through the structure prohibits the structure to achieve any lower-energy, ordered state, even at 1500 °K and at low temperatures, when the driving force for ordering might increase [17]. Meanwhile, MgAl2O4 can be formed from aluminum and magnesium oxides as shown in the following reaction [21]:…”
Section: Resultsmentioning
confidence: 99%
“…Because of their excellent performance, magnesite-chrome refractories are widely used in the burning zone of dry-method cement rotary kilns in the past. However, magnesia chrome bricks are prohibited worldwide, which show a deeply negative impact for Human health and Environment, due to the formation of carcinogenic Cr(VI) species during cement production, so chrome-free refractories have made rapid progress [1][2][3]. Currently, chrome-free refractories are primarily composed of magnesite dolomite bricks, magnesia alumina spinel bricks, magnesia-calcia-zirconia bricks, and Magnesite-hercynite bricks.…”
Section: Introductionmentioning
confidence: 99%
“…Fakat bu tuğlalar bünyelerindeki krom bileşiklerinden dolayı toksik özelliklere sahiptir. Cr +6 iyonlarının deride alerji, ülser ve kansorejen etkisinden dolayı endişe yaratması krom içeren refrakter atıklarının Avrupa Birliği kurallarına göre düzenlenmesini gerektirmiş ve dolayısıyla Cr2O3 içermeyen alternatif refrakter ihtiyacı gündeme gelmiştir [6][7][8]. Bu anlamda yapılan araştırma çalışmaları genel olarak, magnezya-spinel (MgO-MgAl2O4), dolomit ve magnezya-zirkonya tuğlalarının geliştirilmesi üzerinedir.…”
Section: Gi̇ri̇ş ( Introduction )unclassified